Form-focussed Instruction in CALL: What Do Learners Think?. (August 2019) - Khezrlou, Sima
The ways that Iranian universities prepare their students for their future academic and professional lives are changing. Many universities have launched innovative practice in the use of technology in teaching and learning, aiming to present student learners with an engaging experience. The adoption of an innovation necessitates considering the beliefs about it as a substantial part of its integration. The purpose of this study was to explore Iranian university learners' attitudes towards a computerized reading program in promoting vocabulary acquisition and reading comprehension. A total of 52 participants read multi-glossed computerized texts in FonF ( N = 27) and FonFs ( N = 25) conditions. In FonF condition, learners read the texts for comprehension and accessed the multimedia glosses, whereas in FonFs, participants were presented with a word list of the target lexical items prior to on-screen reading. Evidence from both quantitative and qualitative measures unravelled the overall success of the program in bringing about a gradual and consistent improvement in learners' vocabulary learning and reading comprehension. Whereas vocabulary acquisition benefited equally from both FonF and FonFs practices, reading comprehension performance was greater under FonF condition. The effects that each instructional practice had on the different aspects of computer assisted language learning in vocabulary acquisition and reading comprehension are discussed in detail.